Literasi Digital sebagai Tameng: Pencegahan Perilaku Sexting melalui Edukasi Edukatif Di Kabupaten Bulukumba - Arfiani; Bau Kanang; Rahmaniyah R; Fitriani; Jusni (JCS, 2025)
The development of the industrial revolution 4.0 has had a significant impact on the field of information and communication technology, including in the lives of adolescents who are in the phase of searching for identity and sexual exploration. One of the negative impacts of the development of this technology is the emergence of the sexting phenomenon, namely the activity of sending or receiving sexual content via digital devices. This phenomenon is increasingly reflected, especially because many adolescents do not understand the psychological, social, and legal risks of this behavior. This activity aims to increase adolescents' understanding of the dangers of sexting through an educational approach based on digital literacy. The activity was carried out in Bulukumba Regency on May 9, 2025, involving 12 adolescents as participants. The implementation method includes providing a pre-test, delivering educational material about digital security, media ethics, and the impact of sexting, a question and answer session, and a post-test to measure the increase in participants' knowledge. The evaluation results showed a significant increase in adolescents' understanding after participating in the education. Before the activity, only 33% of participants had good knowledge, and increased to 83% after the intervention. Meanwhile, the "sufficient" and "less" categories decreased by 9% and 8% respectively. This finding proves that an educational approach based on digital literacy is effective in forming a wise attitude of teenagers towards the use of digital media.